2013
DOI: 10.1177/0003065112474066
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalysis and Empirical Research

Abstract: An extensive body of research on the alexithymia construct is reviewed to show how various empirical methodologies can be used to evaluate the validity and increase our understanding of theoretical and clinically derived psychoanalytic concepts. The historical background of alexithymia and the theoretical framework in which the construct was formulated are presented, after which measurement- and experiment-based approaches to construct validation are described. This is followed by a review of empirical investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 93 publications
3
114
0
14
Order By: Relevance
“…These results with youths support studies on adult populations that showed that alexithymia is a relevant concept in understanding the onset of difficulties (Taylor and Bagby, 2013;Li et al, 2015). However, research with this population generally found stronger effects for girls between child maltreatment, alexithymia and maladaptive outcomes (Swannell et al, 2012;Brown et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results with youths support studies on adult populations that showed that alexithymia is a relevant concept in understanding the onset of difficulties (Taylor and Bagby, 2013;Li et al, 2015). However, research with this population generally found stronger effects for girls between child maltreatment, alexithymia and maladaptive outcomes (Swannell et al, 2012;Brown et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…The use of self-report measures could possibly have implied informant biases, especially for alexithymia. Indeed questions have been raised about the capacity of alexithymic individuals to accurately report their own deficit of affect awareness (Taylor and Bagby, 2013). Single respondent for all measures is also a limitation of the current study.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
See 3 more Smart Citations